2019
DOI: 10.5114/aoms.2019.82637
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopathy of unknown etiology – is liver biopsy a good tool in differential diagnosis?

Abstract: IntroductionLiver biopsy is a well-known method for the diagnosis and evaluation of chronic diffuse liver diseases, especially among patients with “hepatopathy of unknown origin”.Material and methodsIn the years 2014–2015 we performed 259 liver biopsies in 28 patients (22 females, 6 males, aged 18–65 years, mean: 45 years) with an initial diagnosis of “hepatopathy of unknown origin”. The liver biopsies of these 28 patients were revised by two independent pathologists.ResultsHistopathological features of autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Liver biopsy is not safe for BA children and the obtained histological material is insufficient although it is the gold standard for fibrosis ( 10 ). Liver stiffness measurement (LSM), obtained by shear wave elastography (SWE) has become a reliable and popular non-invasive means in assessing hepatic fibrosis, which has been used for the differential diagnosis of BA ( 11 13 ). At present, elastography is applied in the post-KPE follow-up in some studies, and their LSM values correlate well with the histological stage of liver fibrosis, indicating good performance in the assessment of postoperative liver fibrosis ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liver biopsy is not safe for BA children and the obtained histological material is insufficient although it is the gold standard for fibrosis ( 10 ). Liver stiffness measurement (LSM), obtained by shear wave elastography (SWE) has become a reliable and popular non-invasive means in assessing hepatic fibrosis, which has been used for the differential diagnosis of BA ( 11 13 ). At present, elastography is applied in the post-KPE follow-up in some studies, and their LSM values correlate well with the histological stage of liver fibrosis, indicating good performance in the assessment of postoperative liver fibrosis ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In people whose cancer has spread to other body parts, treatments are mainly aimed at improving the quality of life and comfort of the person [2,3]. Raloxifene or tamoxifen can be administered to inhibit human breast cancer in people who are more likely to get it [5][6][7][8][9]. Chemotherapeutic drugs have severe side effects for the patients, so finding new formulations with low side effects are the priority of the Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic drugs have severe side effects for the patients, so finding new formulations with low side effects are the priority of the Food and Drug Administration. Previous reports have revealed that metallic nanocomposites have unique anticancer efficacies with low side effects [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The main anti-human lung cancer chemotherapeutic supplements/drugs are alectinib, ceritinib, crizotinib, and brigatinib [5]. Due to severe side effects of the chemotherapeutic drugs and supplements, the formulation of the chemotherapeutic medications from Ag nanoparticles are the research priority of pharmacology, oncology, and organic chemistry researchers [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%